EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) DAN THINK PAIR SHARE (TPS) DENGAN STRATEGI TALKING STICK DITINJAU DARI KECERDASAN MAJEMUK SISWA KELAS VII SMPN KOTA SURAKARTA - Kirana, Arinta Rara; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The objectives of research were to find out: 1) which one providing better mathematics learning achievement, TTW by using talking stick model, TPS by using talking stick model or classical learning model, 2) which one providing better mathematics learning achievement, linguistic intelligence, mathematics logic intelligence or interpersonal intelligence, 3) in each multiple intelligence level, which one providing better mathematics learning achievement, TTW by using talking stick model, TPS by using talking stick model or classical learning model, and 4) in each learning models, which one providing better mathematics learning achievement, linguistic intelligence, mathematicslogic intelligence or interpersonal intelligence. This research used the quasi experimental research method. The design of the research was Â 3 Ã 3 factorial. The population was the students of the seven class of Junior High School in Surakarta City on academic year 2014/2015. The tecnique of sampling was stratified cluster random sampling. The proposed hypothesis of the research were tested by using the unbalanced two-way analysis of variance.The conclusions of this research were as follows: 1) TTW by using talking stick model provided better mathematics achievement than TPS by using talking stick model and classical learning model. 2) the mathematics logic intelligence students had mathematics achievement better than linguistic intelligence, the mathematics achievement of linguistic intelligence is the same as interpersonal intelligence, and the mathematics logic intelligence students had mathematics achievement better than interpersonal intelligence. 3) in each of multiple intelligence categories, students mathematics learning achievement is in constancy with result of learning models.4) in each learning models, the students mathematics learning achievement is in constancy withÂ result of multiple intelligence categories.Keywords: TTW, TPS, classical learning, multiple intelligence, talking stick, achievement of learning.